Environmental Ethics- definition, history and ways of development - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Although we think that environmental ethics is something new to our world, and that it exists for past 20 or so years, the truth is much different.debates about this issue last for few decades and fiisrt mentiones about ecology and prоteсtion of the environment are known for a very long time, centuries ago.The environmental ethics was deprived, and not respected, although its significance for the wellbeing of all the humans is bigger every day.In this article, we give a short overview on some of the most promimnent definitions, theories and ways of developing the environmental ethics.